EFFECT CADMIUM EXPOSURE ON RENAL FUNCTION OF WELDING WORKERS - hernayanti, hernayanti; Santoso, Slamet; Lestari, Sri; Prayoga, Lucky; Kamsinah, Kamsinah; Rochmatino, Rochmatino (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2019)
ABSTRACT Cadmium is one of the heavy metals that has nephroxic effect and  dangerous to  human health, especially welding workers. If cadmium enters the body will bind to metallotionein protein.  This process can increase the formation of free radical compounds, thereby induced lipid peroxidation which damage kidney organ and may cause impaired the renal function. Decreased renal function is characterized by an increase of ?2-Microglobulin and creatinine level. The aim of this study are to know effect of Cd exposure to renal function indicated by increasing of Cd, creatinine and ?2-M level. Research design used case control. Research subjects consist of thirty welding workers in Purwokerto with a period of working more than 3 years as case subjects and control subjects come from Pamijen village Baturaden.  Data of Cd, creatinine and ?2-M level were analyzed by t independent. Result of this research showed that in case subjects occur an increase of Cd, creatinine and ?2-M level and have higher level compare with control subjects.It can be concluded that Cd exposure has an effect on renal disfunction which indicated by increasing  blood Cd level, creatinine and ?2-M level.